Performance in France: From appraisal methodologies to ex-post evaluation - Yves Crozet (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
The purpose of this paper is to set out the reasons for this success and, in particular, the propitious environment in which it was achieved: an environment which certainly does not prevail today. Having had the political courage to launch the first high-speed line in Europe, France will no doubt soon have to summon the courage to say that its LGV network is almost complete. However, this will be a difficult decision to take because France nurtures a kind of 'TGV mania' whereby all the regions and most of the large conurbations feel that they must have a high-speed train (TGV) service. The development of high-speed rail in France is a practical experience which has many lessons to offer in terms of the relevance of high-speed rail travel.
Keywords: 330